Inteligência coletiva e redes sociais: uma análise da promoção digital do turismo no destino salvador - CASTRO, Fernanda Meneses de Miranda (2015)
The technology brought a series of changes in human behavior and one of them is the use of social networks as a means of communication. Networks emerged and occupied a living space within the interactive communicability in postmodern society, which aroused the interest of researchers in studying how these relationships occur in multiple areas and entertainment market. In the case of tourism, more specifically, it is noticeable that there was a change in consumer behavior in the market, as the use of social networks allowed, besides the disclosure of destinations, information sharing and collective communication. Therefore, it is important that agencies that plan and promote tourism in the destinations have the perception of the relevance of this phenomenon for the development of the activity and identify how this instrument can be used in order to maximize the opportunities and strengths of locations. Thus, the objective of this research is to evaluate the use of social networks by the bodies responsible for promoting tourism in Salvador and its possible contribution to building a competitive image to the target. To this end, we investigate the importance of the image of a target for the promotion of tourism; It analyzes the development of the promotion of the destination within the state of Bahia tourism planning and the city of Salvador; Search the role that social networks play while sharing instrument and democratization of information for users of pages that promote tourism in Salvador; it examines how digital promotion is crafted in tourism planning Salvador from the analysis of message content available on social networks and, finally, analyzes the perception of the virtual community in relation to the messages available on social networks. The work focuses on the relationship between postmodernity, the information age and tourism. Similarly, search intertwining digital culture and social networks, territorial competitiveness and places marketing and promotion of tourism in Salvador. In order that the objectives are achieved, a sociological approach is made - a study of the social fact generated by computer-mediated communication and the relationships among users of social networks and organizations. The method of procedure is the observation methodology, characterized by being conducted without the intervention of the investigator, in which he only observes and analyzes the object of study. In this case, there is the behavior of users of social networks and administrators of the fate of Salvador pages on Facebook, without intervening or modify any aspect that is being studied. Research techniques are used the Social Network Analysis, Iconologia, Content Analysis and semi-structured interviews. The results suggest that social networks are still a little tool used both in their information supply mechanics, such as the appropriation of this information to generate real action. Conclusively, although preliminary, it is possible to observe that the use of social networks has been considered strategic for the organization and popular mobilization, demonstrating the ability to catalyze reactions in the field of popular political movements. Thus, it is understood that these observed changes also lead to the perception that the fate Salvador can increase the use of this tool as a competitive tool.